(untitled) (Development Service Industry Management, 2024)
The article shows the possibility of improving the technology of self-produced waffle products in the restaurant menu using the example of soft waffles in order to expand the rang of flour confectionery products of increased nutritional value in the menu of restaurants. The purpose of the work is to expand the range of products based on waffle dough in the menu, namely soft waffles of improved quality by: using a mixture of whole wheat flour, defatted flour from chia seeds, matcha tea, pumpkin puree; study of the effect of these additives on the quality of finished products. Standard research methods are used to study structural-mechanical and physico-chemical quality indicators of products. The article search the scientific works of domestic and foreign scientists, provides a literature review on the research topic. The directions of enrichment of products based on waffle dough and the expediency of using whole wheat flour, matcha tea, defatted flour from chia seeds in pumpkin puree in the technologies of bakery, flour confectionery and culinary products are shown. The technology of soft wafers with the specified additives is described. The indicators of the quality of the input raw materials were studied. The research was carried out according to proposed model systems. It was established that sample No. 4 containing 80% whole wheat flour, 19% defatted chia seed flour, 1% matcha tea according to model system No. 1, has the best organoleptic quality indicators: products with additives are well baked, without compactions, has the correct a shape that corresponds to the shape of the product, without a burnt surface, a taste of pumpkin puree and a herbal aroma. It is known that waffle products contain a significant amount of fat in their composition. Adding pumpkin puree to the recipe of soft waffles to replace the fat component of the recipe is justified. The results showed that the sample with 20% pumpkin puree has the best quality indicators: the product has preserved a uniform porous structure of the crumb and the correct clear shape. A further direction of research is the justification of the use of various types of plant raw materials of increased nutritional value in the technologies of flour confectionery and culinary products with the aim of expanding the segment of products of own production in the restaurant menu.